Inflation Risk Analysis of European Real Estate Securities - Raimond Maurer; Steffen Sebastian (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 2002)
The focus of this article is the analysis of the inflation risk of European real estate securities. Following both a causal and a final understanding of risk, the analysis is twofold. First, to examine the causal influence of inflation on short- and long-term asset returns, different regression approaches are employed based on the methodology of Fama and Schwert (1977). Hedging capacities against expected inflation are found only for German open-end funds. Secondly, different shortfall risk measures are used to study whether an investment in European real estate securities protects against a negative real return at the end of a given investment period.
urn:nbn:de:hebis:30-18524
Keywords: 330; Pfandbrief; Immobilienfonds; Portfolio-Management; Rendite; Inflation; Risiko; Schätzung; Frankreich; Deutschland; Großbritannien; Schweiz